1978
DOI: 10.2134/agronj1978.00021962007000030007x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of K on the Uptake, Translocation, and Reduction of Nitrate by Barley Seedlings1

Abstract: The absorption, translocation, and metabolism of N is influenced by the source of N and by the availability and mobility of counter ions for transport. The purpose of this study was to determine the influence of K or Ca on nitrate uptake, translocation, and reduction in barley seedlings (Hordeum vulgare. cv. Compana). Six‐day‐old barley seedlings were grown for 2 to 36 hours in solutions of 1.0 meq/liter KNO3 or Ca(NO3)2, each containing 0.4 meq/liter of CaSO4. Experiments were conducted in a growth chamber at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…Minotti et al (15) have shown that N03-uptake and translocation were impaired in the absence of either K+ or Ca2+. Blevins et al (4) showed that in roots of barley seedlings treated with Ca(NO3)2, N03-accumulation, organic acid accumulation, and NRA were much less than in KNO3-treated seedlings. Shaner and Boyer (19,20), by using NO3 depletion and cooling of roots and water stress, showed that the decrease in leaf NRA was due to decreased N03 flux to leaves.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Minotti et al (15) have shown that N03-uptake and translocation were impaired in the absence of either K+ or Ca2+. Blevins et al (4) showed that in roots of barley seedlings treated with Ca(NO3)2, N03-accumulation, organic acid accumulation, and NRA were much less than in KNO3-treated seedlings. Shaner and Boyer (19,20), by using NO3 depletion and cooling of roots and water stress, showed that the decrease in leaf NRA was due to decreased N03 flux to leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Minotti et al (15) showed that wheat seedlings absorbed no more N03 from KNO3 solution in the absence of Ca2" than from Ca(NO3)2 solution. In the presence of CaSO4, N03 u?take and assimilation were much greater with K+ than with Ca + as the countercation (4 …”
mentioning
confidence: 89%
See 1 more Smart Citation
“…An interaction between K+ and NO3 at all stages of nitrate metabolism, beginning with the uptake by roots (4,5,13) until the synthesis of protein (17,24,25) has been confirmed in a few autotrophic species. But the mechanisms involved in the K-induced promotion of NRA' and protein synthesis remain to be explained.…”
mentioning
confidence: 92%
“…Blevins et al (1978) mentioned that K has an important role as a counter ion for the uptake and translocation of nitrate (NO3 -) within the plant. Foliar K sprays can be an effective method to shorten the time required for uptake compared to soil application (Embleton et al ., 1969) .…”
Section: -3 Fe Mn Zn and Cu Leaf Contents (Ppm)mentioning
confidence: 99%